Evolution of Ycf54-independent chlorophyll biosynthesis in cyanobacteria - Chen, Guangyu E; Hitchcock, Andrew; Mareš, Jan; Gong, Yanhai; Tichý, Martin; Pilný, Jan; Kovářová, Lucie; Zdvihalová, Barbora; Xu, Jian; Hunter, C Neil; Sobotka, Roman (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Chlorophylls (Chls) are essential cofactors for photosynthesis. One of the least understood steps of Chl biosynthesis is formation of the fifth (E) ring, where the red substrate, magnesium protoporphyrin IX monomethyl ester, is converted to the green product, 3,8-divinyl protochlorophyllide a In oxygenic phototrophs, this reaction is catalyzed by an oxygen-dependent cyclase, consisting of a catalytic subunit (AcsF/CycI) and an auxiliary protein, Ycf54. Deletion of Ycf54 impairs cyclase activity and results in severe Chl deficiency, but its exact role is not clear. Here, we used a Δycf54 mutant of the model cyanobacterium Synechocystis sp. PCC 6803 to generate suppressor mutations that restore normal levels of Chl. Sequencing Δycf54 revertants identified a single D219G amino acid substitution in CycI and frameshifts in slr1916, which encodes a putative esterase. Introduction of these mutations to the original Δycf54 mutant validated the suppressor effect, especially in combination. However, comprehensive analysis of the Δycf54 suppressor strains revealed that the D219G-substituted CycI is only partially active and its accumulation is misregulated, suggesting that Ycf54 controls both the level and activity of CycI. We also show that Slr1916 has Chl dephytylase activity in vitro and its inactivation up-regulates the entire Chl biosynthetic pathway, resulting in improved cyclase activity. Finally, large-scale bioinformatic analysis indicates that our laboratory evolution of Ycf54-independent CycI mimics natural evolution of AcsF in low-light-adapted ecotypes of the oceanic cyanobacteria Prochlorococcus, which lack Ycf54, providing insight into the evolutionary history of the cyclase enzyme.
Keywords: bakteriální proteiny; delece genu; Synechocystis; bakteriochlorofyly; chlorophyll; cyanobacteria; Prochlorococcus; oxygenasy; Oxygenases; microevolution; Bacterial Proteins; cyclase; Gene Deletion; photosynthesis; Bacteriochlorophylls